The comparison of the unilateral and bilateral resistance training in young handball players - Pori, P.; Martinc, D.; Sibila, M.; Stirn, I. (Sport Sciences for Health, 2023)
Purpose Performing resistance exercises unilaterally, athletes must activate stabilizing muscles to maintain balance position, and for the same relative load, compressive forces on the spine are reduced providing more safety. Our aim was to compare the effects of resistance training when bilateral and unilateral exercises were used.